2009
DOI: 10.2174/157016209787581508
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr: A Closer Look at the Multifunctional Protein from the Structural Perspective

Abstract: The human immunodeficiency virus-1 (HIV-1) Vpr protein plays multiple roles in HIV-1 replication. In early infection, Vpr provides help in the nuclear localization of pre-integration complex. Subsequently, Vpr induces cell cycle arrest of infected cells at G2/M phase. Cell cycle arrest facilitates higher rate of viral gene transcription. Vpr is also capable of activating transcription of viral and heterologous genes. Vpr induces apoptosis in infected cells leading to loss of immune cells and onset of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Vpr is packaged into the virion, and is essential for HIV-1 replication in macrophages (8,9). Infected brain cells have been shown to release Vpr that could affects neuronal growth (10).…”
mentioning
confidence: 99%
“…Vpr is packaged into the virion, and is essential for HIV-1 replication in macrophages (8,9). Infected brain cells have been shown to release Vpr that could affects neuronal growth (10).…”
mentioning
confidence: 99%
“…Extensive studies have shown that coactivation of glucocorticoid receptor by Vpr, resulting in transcription of elements in the promoter regions of the HIV LTR and host genes, enhances viral replication and downregulates host immune responses Hapgood and Tomasicchio, 2010). Vpr also drives apoptosis and G2 cell cycle arrest (Morellet et al, 2009;Pandey et al, 2009;Tungaturthi et al, 2004). The processes enhance immune escape and HIV-1 replication, respectively.…”
Section: Polymorphisms In Specific Hiv-1 Genesmentioning
confidence: 99%
“…Hyper-phosphorylation inactivates Cdc2-Cyclin B1 to prevent cell division. This process arrests the cell in the G2 phase (Morellet et al, 2009;Pandey et al, 2009;Sherman et al, 2002). Vpr expression in various cell types leads to G2 cell cycle arrest.…”
Section: G2 Cell Cycle Arrestmentioning
confidence: 99%
“…However, another report showed that Vpr triggers activation of Chk1 (a cell cycle checkpoint control kinase) through Ser 345 phosphorylation in an S phase-dependent manner, subsequently leading to G 2 arrest (18). These two examples, along with others (6,7,19), illustrate more than one potential cell cycle arrest mechanism for Vpr. To complicate matters, Vpr has also been shown to bind to nucleic acids, implying its regulatory role in viral and cellular transcription machineries (20,21).…”
mentioning
confidence: 98%
“…The Vpr gene is highly conserved in all HIV and Simian immunodeficiency virus members of the lentivirus family (4), denoting the importance of this gene in viral assault. The modest structure of the Vpr protein, three ␣-helices flanked by two flexible regions, belies its numerous roles in the virus life cycle and its effects on infected host cells (5)(6)(7). Vpr has been found to hijack various cellular pathways thought to be independent of one another, such as G 2 cell cycle arrest, apoptosis, nuclear import, retrotranscription, the integration of the provirus in the nucleus, and transactivation of HIV-1 long terminal repeats (1,3).…”
mentioning
confidence: 99%